GAMBARAN PERILAKU IBU HAMIL DALAM PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS BANJARANGKAN I KLUNGKUNG - Cahyanti, Ni Luh Sumi; Dewi, I Gusti Agung Ayu Novya; Armini, Ni Wayan (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023, 2023)
ABSTRACT The low literacy level of pregnant women regarding the use of the MCH Handbook which only functions as a note-taking tool for health providers is an obstacle to shaping and changing health behavior. The expected output in a short period is an increase in knowledge about Antenatal Care and in a long period the behavior of the mother's health can change for the better as well. The purpose of this study was to describe the behavior of pregnant women in utilizing the MCH Handbook at the Regional Technical Implementation Unit of the Banjarangkan I Health Center, Klungkung. This type of research is descriptive observational. The research was conducted in February-May 2023. The total sample was 66 respondents. The sample collection technique is purposive sampling. Data collection method with a questionnaire. The results showed that 42.4% of pregnant women had sufficient knowledge, 75.8% of pregnant women had a positive attitude in using the MCH handbook, 84.8% of pregnant women took action in using the MCH handbook. It is hoped that all relevant parties can support the use of the MCH handbook for the health of pregnant women and their wombs. Keywords: Maternal and Child Health Books, behavior mother pregnacy